Water as a pedogenetical factor in the river basin of Sotla - Prah, Klemen (Journal for Geography, 2012)
Soil develops on the contact of all components of the landscape, including hydrosphere. We want to find out, how water resources in Sotla river basin contribute to soil characteristics. This knowledge is important for land use orientation and consequently for soil protection. For this purpose we studied Sotla river basin as region, which is divided on five hydrographical areas. We compared them according to water and pedological characteristics considering land use. The accent was on GIS methodology. Sotla river basin is located along Slovenian-Croatian border and is very asymmetric. The river network is very dense, present are also many standing waters. From land use predominate forests followed by grasslands, fields, built-up areas, vineyards, orchards, trees and bushes, swamps and marsh grasslands. From the soils predominate eutric and distric brown soils, in hills rendzina, ranker and brown soils on limestone. Vineyard sites cover anthropogenic soils. In river valleys are spread riverine soils on clay, gleyed and pseudogleyed soils. Surface waters in Sotla river basin are highly subjected to human act and have great influence on soils. That reflects in land use. It can be recognized in high percent of agriculture fields, the most extensive on holocen flat lands along rivers Sotla, Mestinjščica and Bistrica, where predominate hydromorfic soils.
Keywords: geography; water resources; soil; Sotla river basin